An actualistic butchery study in South Africa and its implications for reconstructing hominid strategies of carcass acquisition and butchery in the upper pleistocene and plio-pleistocene - Nilssen, Peter John (Department of Archaeology, 2024)
An actualistic butchery study in South Africa and its implications for reconstructing hominid strategies of carcass acquisition and butchery in the upper pleistocene and plio-pleistocene